Inhibition of Type 1 Iodothyronine Deiodinase by Bisphenol A - da Silva, Maurício Martins; Gonçalves, Carlos Frederico Lima; Miranda-Alves, Leandro; Fortunato, Rodrigo Soares; Carvalho, Denise P.; Ferreira, Andrea Claudia Freitas (Hormone and Metabolic Research, 2019)
Plastics are ubiquitously present in our daily life and some components of plastics are endocrine-disrupting chemicals, such as bisphenol A and phthalates. Herein, we aimed to evaluate the effect of plastic endocrine disruptors on type 1 and type 2 deiodinase activities, enzymes responsible for the conversion of the pro-hormone T4 into the biologically active thyroid hormone T3, both in vitro and in vivo. Initially, we incubated rat liver type 1 deiodinase and brown adipose tissue type 2 deiodinase samples with 0.5 mM of the plasticizers, and the deiodinase activity was measured. Among them, only BPA was capable to inhibit both type 1 and type 2 deiodinases. Then, adult male Wistar rats were treated orally with bisphenol A (40 mg/kg b.w.) for 15 days and hepatic type 1 deiodinase and brown adipose tissue type 2 deiodinase activities and serum thyroid hormone concentrations were measured. In vivo bisphenol A treatment significantly reduced hepatic type 1 deiodinase activity but did not affect brown adipose tissue type 2 deiodinase activity. Serum T4 levels were higher in bisphenol A group, while T3 remained unchanged. T3/T4 ratio was decreased in rats treated with bisphenol A, reinforcing the idea that peripheral metabolism of thyroid hormone was affected by bisphenol A exposure. Therefore, our results suggest that bisphenol A can affect the metabolism of thyroid hormone thus disrupting thyroid signaling.
Keywords: plastic; endocrine disruptor; deiodination; thyroid